Answer:
x = 2
Explanation:
= -x + 2 Multiple both sides by 3
![((3)/(1))](https://img.qammunity.org/2023/formulas/mathematics/middle-school/89bnb0qkj9vu2h7e8jgt39zal2le3lejv8.png)
= (3)(-x + 2)
5(x -2) = -3x + 6 Distribute the 5
5x - 10 = -3x + 6 Add 3x to both sides
5x + 3x - 10 = -3x + 3x + 6
8x -10 = 6 Add 10 to both sides
8x - 10 + 10 = 6 + 10
8x = 16 Divide both side by 8
=
![(16)/(8)](https://img.qammunity.org/2023/formulas/mathematics/high-school/pj2swm58rks5u2gkpj8vi1ewlnovw929pq.png)
x = 2